Vertical axis current turbine using arm and self-adjusting blade angle for low speed current - Behrouzi, Fatemeh (2017)
Utilization of electrical energy is important for economic growth and improvement of people's living, especially for rural and remote areas which have access to the water but lack of electricity supply. It is known that global energy, especially in developing countries such as Malaysia, is still heavily dependent on fossil fuels, which are costly, cause environmental pollution and rapidly depleting. Hydrokinetic energy, which is one of green and environmentally friendly energy resources, is promising to replace fossil fuels for electricity generation. The objectives of this research are firstly to investigate the effect of arm on torque coefficient of turbine in low speed current, and secondly to determine the effect of self-adjusting blades on power coefficient. Numerical and experimental research methodologies have been applied to achieve the objectives. RANS equations have been applied in CFD simulations using ANSYS-CFX commercial code. For validation of the simulation results, towing tank experiments using fixed blades condition to obtain suitable arm length have been carried out at the Marine Technology Centre (MTC)- Universiti Teknologi Malaysia (UTM). Based on the results obtained by fixed blades condition, a series of test using self-adjusting blades have been done in three conditions of load at different current speeds to determine the performance of turbine. The results show that the arm length and blades angle have a strong effect on the performance of turbine, where there is 23% increase in terms of performance of selfadjusting blades turbine compared to fixed blades turbine. This is because the returning blade angle is in closed position which decreases the hydrodynamic resistance. In addition, the advancing blade angle is in open condition to have the maximum force acting. The combined effects result in the increase of torque by the turbine. The maximum efficiency of the modified self-adjusting system was 16% at tip speed ratio, λ=0.45. The developed turbine can be applied as a useful tool for electricity generation in low speed currents. It could also be integrated with a wide range of generators with different loads.